Transmission and immunopathology of the avian influenza virus A/Anhui/1/2013 (H7N9) human isolate in three commonly commercialized avian species. (14th September 2017) - Vidaña, B.; Dolz, R.; Busquets, N.; Ramis, A.; Sánchez, R.; Rivas, R.; Valle, R.; Cordón, I.; Solanes, D.; Martínez, J.; Majó, N.
Summary: H7N9 virus infection is a global concern, given that it can cause severe infection and mortality in humans. However, the understanding of H7N9 epidemiology, animal reservoir species and zoonotic risk remains limited. This work evaluates the pathogenicity, transmissibility and local innate immune response of three avian species harbouring different respiratory distribution of α2, 6 and α2, 3 SA receptors. Muscovy ducks, European quails and SPF chickens were intranasally inoculated with 10 5 embryo infectious dose (EID)50 of the human H7N9 (A/Anhui/1/2013) influenza isolate. None of the avian species showed clinical signs or macroscopic lesions, and only mild microscopic lesions were observed in the upper respiratory tract of quail and chickens. Quail presented more severe histopathologic lesions and avian influenza virus (AIV) positivity by immunohistochemistry (IHC), which correlated with higher IL‐6 responses. In contrast, Muscovy ducks were resistant to disease and presented higher IFNα and TLR7 response. In all species, viral shedding was higher in the respiratory than in the digestive tract. Higher viral shedding was observed in quail, followed by chicken and ducks, which presented similar viral titres. Efficient transmission was observed in all contact quail and half of the Muscovy ducks, while no transmission was observed between chicken. All avian species showed viral shedding in drinking water throughout infection.